Trade Liberalization and Industry Wage Structure : Evidence from Brazil - Pavcnik, Nina; Blom, Andreas; Goldberg, Pinelopi; Schady, Norbert (Washington, DC: World Bank, 2014)
Industry affiliation provides an important channel through which trade liberalization can affect worker earnings and wage inequality between skilled and unskilled workers. This empirical study of the impact of the 1988-94 trade liberalization in Brazil on the industry wage structure suggests that although industry affiliation is an important component of worker earnings, the structure of industry wage premiums is relatively stable over time. There is no statistical association between changes in industry wage premiums and changes in trade policy or between industry-specific skill premiums to university graduates and trade policy. Thus trade liberalization in Brazil did not significantly contribute to increased wage inequality between skilled and unskilled workers through changes in industry wage premiums. The difference between these results and those obtained for other countries (such as Colombia and Mexico) provides fruitful ground for studying the conditions under which trade reforms do not have an adverse effect on industry wage differentials